2008
DOI: 10.1194/jlr.m800238-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol accumulation and diabetes in pancreatic β-cell-specific SREBP-2 transgenic mice: a new model for lipotoxicity

Abstract: To determine the role of cholesterol synthesis in pancreatic b-cells, a transgenic model of in vivo activation of sterol-regulatory element binding protein 2 (SREBP-2) specifically in b-cells (TgRIP-SREBP-2) was developed and analyzed. Expression of nuclear human SREBP-2 in b-cells resulted in severe diabetes as evidenced by greater than 5-fold elevations in glycohemoglobin compared with C57BL/6 controls. Diabetes in TgRIP-SREBP-2 mice was primarily due to defects in glucose-and potassium-stimulated insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 44 publications
9
91
0
3
Order By: Relevance
“…The principal targets for phosphorylation by AMPK are Hmgcr and Acaca (Towler & Hardie 2007). Interestingly, Srebf2 gene is tightly associated with the regulation of a number of genes encoding for enzymes involved in the CH biosynthetic pathway (Ishikawa et al 2008). Our RT-PCR results showed that leucine upregulated expressions of CH biosynthetic enzymes, e.g.…”
Section: Discussionmentioning
confidence: 58%
“…The principal targets for phosphorylation by AMPK are Hmgcr and Acaca (Towler & Hardie 2007). Interestingly, Srebf2 gene is tightly associated with the regulation of a number of genes encoding for enzymes involved in the CH biosynthetic pathway (Ishikawa et al 2008). Our RT-PCR results showed that leucine upregulated expressions of CH biosynthetic enzymes, e.g.…”
Section: Discussionmentioning
confidence: 58%
“…This negative effect on b-cell function due to accumulation of cholesterol has also been shown in the overactivation of its sources. SREBP2 regulates the expression of HMG-CoA reductase and LDL receptor, and its overexpression increases cholesterol content, compromising islet morphology and GSIS in mouse islets (Ishikawa et al 2008). Thus, not only cholesterol reduction but also a dramatic increase in cholesterol content has been shown to reduce insulin secretion (Kruit et al 2011, Souza et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Among these parameters, triglycerides (TG), which are particularly influenced by insulin resistance 6) , represent an independent risk factor for DM [7][8][9][10][11][12][13][14][15] . Lipotoxicity, which results from the accumulation of lipids in the skeletal muscle, liver and pancreas, plays an important role in the onset of insulin resistance and β-cell damage 16,17) . Although current guidelines recommend measuring the lipid levels in a fasting state, recent studies suggest that non-fasting lipid profiles may be useful in the clinical setting 18) .…”
Section: Introductionmentioning
confidence: 99%